Writing the Social History of Labor in the Iranian Oil Industry. (7th January 2014) - Atabaki, Touraj
<x content-type="archive" xml:space="preserve">Abstract</x> Over the course of the twentieth century, Iran has experienced numerous dramatic events and has undergone radical transformations. The country participated in three major wars (1914–1918, 1941–1945, 1980–1988) that caused enormous human suffering and economic damage; two coup détats (1921, 1953) that altered power relations within the military and political elite; and two revolutions (1905–1909, 1978–1982) that led to fundamental changes in social, political, and cultural relations in Iran and beyond. But the event that, perhaps, has had the most significant impact on the history of twentieth-century Iran was the discovery of oil in 1908.